From impression to addiction: The pathways of adolescent tobacco use - Parth R Pandya; Tejas C Vaja; C Arjun; Radhika P Vijayan; Shipha Hegde; Shivani Kataria; Sheron Jokhi (Wolters Kluwer Medknow Publications, 2024)
Aim: To understand the psychodynamics of tobacco use among 11- to 14-year-olds in Ahmedabad, India. Materials and Methods: A self-administered questionnaire was used to gather information on tobacco use from 5,266 students, aged 11 to 14, enrolled in government-aided English medium schools in Ahmedabad. IBM® SPSS® 26.0 software along with Chi-square tests were used to analyze the data. Results: A total of 7.2% (376) had ever used tobacco. Of the users, 96.6% (363) knew it was harmful, 76.3% (287) were boys, and 85.2% (320) were initiated by family and friends. Conclusion: Despite being aware of the dangers of tobacco and being unable to purchase from vendors, children continued to obtain tobacco products, being influenced by their close social networks. An effective cessation measure should be directed toward this psychodynamic etiology.